Optimization of the proportions of advantageous components in the hypolipidemic "bioequivalent substance system" of Jiang-Zhi-Ning and its mechanism of action - Yumiao Li; Yan Zhang; Yu Zhang; Tianfeng Lin; Yanyan Gao; Yuan Cai; Chang Zhou; Leyi Yang; Bin Liu; Shifen Dong; Yanyan Jiang (Taylor & Francis Group, 2023)
AbstractContext Jiang-Zhi-Ning (JZN), a traditional Chinese medicinal formula, is used to treat hyperlipidemia in clinics.Objective To screen the hypolipidemic "bioequivalent substance system (BSS)" of JZN and elucidate the potential hypolipidemic mechanism.Materials and methods In vitro, the TG content in HepG2 cells was determined after the intervention of the combination of advantageous components (CAC) by uniform design. In vivo, hyperlipidemia models were established by Triton WR-1339 (400 mg/kg; i.p.) in male ICR mice, and corresponding treatments were administered via oral administration once. The mice were divided into 12 groups (n = 5): control, hyperlipidemic model, simvastatin (positive control, 20 mg/kg), gradient doses of JZN granules (2, 4 and 8 g/kg) and the hypolipidemic effective extraction (HEE) of JZN (120, 240 and 480 mg/kg) and CAC groups (20, 40 and 160 mg/kg). Serum TC, TG, LDL-C and HDL-C were performed after 24 h. Transcriptomics and qRT-PCR technology were used to explore the mechanism of the "BSS" of JZN.Results In vitro, the ratio of CAC was determined. CAC could reduce the TG content in HepG2 cells (77.21%). Compared with the model group, the high dose of CAC could markedly decrease the levels of TC (61.86%), TG (105.54%) and LDL-C (39.38%) and increase the level of HDL-C (232.67%). CAC was proved to be the "BSS". Transcriptomics and qRT-PCR analysis revealed CAC regulated non-alcoholic fatty liver disease, bile secretion, PPAR and adipocytokine signalling pathway.Discussion and conclusions These findings provided new feasible ideas and methods for the elucidation of the pharmacodynamic material basis.